Delayed sequential abdominal wall closure in pediatric liver transplantation to overcome "large for size" scenarios. (2nd September 2021) - Molino, José Andrés; Hidalgo, Ernest; Quintero, Jesús; Coma, Ana; Ortega, Juan; Juamperez, Javier; Mercadal‐Hally, María; Riera, Lluis; Riaza, Lucia; Bilbao, Itxarone; Dopazo, Cristina; Caralt, Mireia; et al.
Abstract: Background: Primary abdominal wall closure after pediatric liver transplantation (PLT) is neither always possible nor advisable, given the graft‐recipient size discrepancy and its potential large‐for‐size scenario. Our objective was to report the experience accumulated with delayed sequential closure (DSC) guided by Doppler ultrasound control. Methods: Retrospective analysis of DSC performed from 2013 to March 2020. Results: Twenty‐seven DSC (26.5%) were identified out of 102 PLT. Transplant indications and type of grafts were similar among both groups. In patients with DSC, mean weight and GRWR were 9.4 ± 5.5 kg (3.1–26 kg) and 4.7 ± 2.4 (1.9–9.7), significantly lower and higher than the primary closure cohort, respectively. The median time to achieve definitive closure was 6 days (range 3–23 days), and the median number of procedures was 4 (range 2–9). Patients with DSC had longer overall PICU (22.5 ± 16.9 vs. 9.1 ± 9.7 days, p  < .05) and hospital stay (33.4 ± 19.1 vs 23, 9 ± 19.8 days ( p  < .05). These differences are less remarkable if the analysis is performed in a subgroup of patients weighing less than 10 kg. Two patients presented vascular complications (7.4%) within DSC group. No differences were seen when comparing overall, 3‐year graft and patient survival (96% and 96% in the DSC group). Conclusions: DSC is a simple and safe technique to ensure satisfactory clinical outcomes to overcome "large for size" scenarios in PLT. In addition, we were able to avoid using a permanent biological material for closing the abdomen.